PENDEKATAN EMOTIONAL DEMONSTRATION DALAM UPAYA PENINGKATAN PRAKTEK PERILAKU HIDUP BERSIH DAN SEHAT SUKU ANAK DALAM DI DESA PELAKAR JAYA - M. Ridwan; La Ode Reskiaddin; Vinna Rahayu Ningsih; Puspita Sari (Jurnal Salam Sehat Masyarakat (JSSM), 2020)
Health problems related to clean and healthy living habits are one of the problems that still occur in tribal communities. Based on the results of the initial survey, behavioral aspects, especially the hygiene of individual ethnic children in Pelakar Jaya village, are still lacking, especially the cleanliness of clothes and bodies. In addition, the housing environment is not clean and healthy because there are still lots of garbage scattered about. Efforts can be made to overcome this problem through education with an emotional demonstration approach regarding PHBS. This education aims to increase knowledge and practices related to personal and environmental hygiene. This community service was carried out in Pelakar Jaya Village, Pelepat District, Merangin Regency by 4 lecturers and 5 students. The results of the activity showed that there was an effect of emotional demonstration on increasing community knowledge and skills regarding Clean and Healthy Living Behaviors, especially indicators of washing hands with soap. The need for continuous socialization and monitoring by health center personnel regarding clean and healthy living habits.